Intra-African trade in virtual water: Trends and drivers - Matchaya, Greenwell C.; Odjo, Sunday; Collins, Julia (International Food Policy Research Institute, 2024)
Increasing intra-African trade is expected to have a wide range of benefits, including contributing to increased economic growth, employment, and food security. The African Continental Free Trade Area (AfCFTA), launched in 2021, will have potentially significant impacts on economic output and incomes when fully implemented. A recent study suggests that AfCFTA implementation will drive substantial employment growth, generating more than 7 million new jobs in manufacturing, public services, trade, and other services (World Bank 2020). Bouët, Laborde, and Traoré (2022) estimate that an ambitious implementation of the AfCFTA, which eliminates tariffs and significantly reduces nontariff measures, would increase Africa’s gross domestic product (GDP) by 0.2 percent compared to baseline trends in the absence of the AfCFTA by 2035. Increased intra-African trade in agriculture could also contribute significantly to improving food security and nutrition, including by increasing dietary diversity, promoting food price stability, and boosting the availability of key micronutrients (Bonuedi, Kamasa, and Opeku 2020; Makochekanwa and Matchaya 2019; Odjo and Badiane 2018; Olivetti et al. 2023). A further potential benefit of increased intra-African trade is its contribution to environmental sustainability and efficient use of scarce natural resources. The impacts of trade on the environment are complex. Although trade expends resources and contributes to greenhouse gas emissions, it could also contribute to sustainable resource use if it allows countries to specialize in production patterns according to their resource endowments and comparative advantage (Odjo, Traoré, and Zaki 2023). In the context of climate variability and water scarcity, trade could potentially help to minimize the negative impacts by moving commodities from areas with high water availability to water-scarce areas (Matchaya, Garcia, and Traoré 2023). This chapter reviews overall trends in intra-African agricultural trade and, to assess the contribution of this trade to sustainability, takes a close look at its potential to address issues of water scarcity and contribute to efficient use of water resources. The chapter examines intra African agricultural trade in virtual water—that is, the water content embedded in trade flows of agricultural products. Trade is most commonly measured in value terms, but the monetary value of a product does not always reflect the resources used to produce it. Trade flows expressed as virtual water trade (VWT) reflect both the specific water requirements of different crops and the varying crop yields obtained in different countries. Examining intra-African trade in virtual water terms and identifying the impact of countries’ resource endowments and water productivity levels on VWT helps us to assess the contribution of intra-African trade to addressing water stress and scarcity in African countries and contributing to more efficient water use.